Comprehensive analysis of sediment grain features and their engineering implications in the Yangtze River source area - Li, Zhijing; Wang, Xiaoxue; Liu, Yujiao; Li, Wenqi; Zhou, Xian; Lv, Chaonan; Wang, Guiqiao; Ma, Junxiao (Frontiers in Soil Science, 2025)
IntroductionThe particle size characteristics of irregular sediments in the Yangtze River Source Area (YRSA) are pivotal for understanding the mechanical properties of the sedimentary medium.MethodsThis study utilizes field sediment sampling, laser scanning, laboratory testing, and mathematical statistics to analyze the morphological, geometric, mineralogical, and accumulation characteristics of sediment particles in the region.ResultsOur findings indicate that sediments in the YRSA have angular edges and deviate from spherical shapes, exhibiting elongated and flatter three-dimensional morphologies. In the experiment, the sliding plate method was used to measure the angle of repose of the sediments, which was found to be 36.7° above water and 35.9° below water. Both values are higher than the typical range for non-plateau regions, indicating reduced sediment mobility. The sediments are composed of fine-grained and coarse-grained soils. The particle size distribution is primarily coarse sand (0.5-2.0 mm), fine gravel (2.0-5.0 mm), and medium gravel (5.0-20.0 mm), with a significant coarsening trend observed over the past six years. The mineral composition, dominated by quartz, feldspar, and heavy minerals, is stable, with approximately 70% of the minerals having a hardness of ≥ 7 on the Mohs scale. The most abundant trace elements are Ti, Mn, Ba, P, Sr, Zr, and Cl.DiscussionThis research reveals that the sediment characteristics in the YRSA are markedly different from those of natural sands in non-plateau regions, necessitating a reevaluation of conventional theories and engineering practices for engineering constructions in this area. The insights from this study are profound and practically relevant, illuminating the sediment transport dynamics in alpine river systems and supporting sustainable regional development.